Key Implications of the Dodd-Frank Act for Independent Regulatory Agencies - Joel Seligman (Washington University Law Review, 2011)
The enactment of the Dodd-Frank Wall Street Reform and Consumer Protection Act both transcends and transforms financial regulation. The immediate setting of the law is by now a familiar one. By 2008, there was an urgent need for a fundamental restructuring of federal financial regulation, primarily based on three overlapping causes. First, an ongoing economic emergency initially rooted in our housing and credit markets, which has been succeeded by the collapse of several leading investment and commercial banks and insurance companies, dramatic deterioration of our stock market indices, and a rapidly deepening recession. Second, serious breakdowns in the enforcement and fraud deterrence missions of federal financial regulation, as illustrated by matters involving Bear Stearns and the other four then independent investment banks subject to the SEC’s former Consolidated Supervised Entities program, led to the government creation of conservatorships for Fannie Mae and Freddie Mac and the Bernard Madoff case. Third, a misalignment between federal financial regulation firms and intermediaries. The structure of financial regulation that was developed during the 1930s did not keep pace with fundamental changes in finance.
Keywords: Financial institutions; Independent regulatory commissions; United States. Financial Stability Oversight Council; United States. Securities and Exchange Commission; Dodd-Frank Wall Street Reform and Consumer Protection Act of 2010; United States